Anticipatory Postural Adjustments During Gait Initiation in Stroke Patients - Delafontaine, Arnaud; Vialleron, Thomas; Hussein, Tarek; Yiou, Eric; Honeine, Jean-Louis; Colnaghi, Silvia (Frontiers in Neurology, 2019)
Prior to gait initiation (GI), anticipatory postural adjustments (GI-APA) are activated in order to reorganize posture in a favourable way for gait. In healthy subjects, the centre of pressure (CoP) is displaced backward during GI-APA, bilaterally by reducing soleus activities and activating the tibialis anterior (TA) muscles, and laterally in the direction of the leading leg by activating hip abductors. In post-stroke hemiparetic patients, TA, soleus and hip abductor activities are impaired on the paretic side. Reduction in non-affected triceps surae activity can also be observed. These may result in a decreased ability to execute GI-APA and to generate propulsion forces during step execution. A systematic review was conducted to provide an overview of the reorganization occurring in GI-APA following stroke and of the most effective strategies for tailoring gait-rehabilitation to these patients. Sixteen articles were included, providing gait data from a total of 220 patients. Stroke patients show a decrease in the TA activity associated with difficulties in silencing soleus muscle activity of the paretic leg, a decreased CoP shift, lower propulsive anterior forces and a longer preparatory phase. Regarding possible gait-rehabilitation strategies, the selected studies show that initiating gait with the paretic leg provides poor balance. The use of the non-paretic as the leading leg can be a useful exercise to stimulate the paretic postural muscles.